Membangun Pemahaman Mahasiswa Calon Guru Akan Interaksi Dalam Pembelajaran Melalui Program Pengalaman Lapangan-1 Di Sekolah - Melda Jaya Saragih; Kurnia Putri Sepdikasari Dirgantoro; Meiva Marthaulina Lestari Siahaan (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2021)
The purpose of the research is to describe the process of establishing students teachers' understanding about interactions in learning, describing those various understandings obtained as results of the field ecperience (PPL 1), how tasks and stages are designed according to the blue print of PPL1 to create holistic learning for prospective students of mathematics education teachers. The research method was descriptive qualitative by analyzing in depth the results of written interviews of students, through their reflections, and student observation sheets consisting of 30 students of mathematics education disseminated in several Christian schools. The data was validated with triangulation techniques, namely interviews, student reflections and student portfolios. In PPL 1, students observe and collaborate with mentor teachers and are directly involved in one-week learning activities. Through the journal of reflection students also help students to develop their understanding of the responsibility of the teacher and give direction for students can take steps to improve in the future if later become a teacher in the school. Students gained new understanding of interaction in the classroom, i.e. students understand the important of teachers to greet students before starting learning, the use positive words, recognize student names, show students' involvement in learning. Teacher students got good example and were prepared to be teachers who can build students' personal through interactions formed by teachers in the classroom. In addition, students also understood the steps to build good interaction with students. The implementation of PPL-1 is monitored in a structured manner, students were placed in a school environment that maximizes them to learn the correct practices and values of Christian education from teachers, principals, school environments and lecturers.